Combining total laparoscopic hysterectomy and bilateral salpingo-oophorectomy with subcutaneous mastectomy in trans men: The effect on safety outcomes. Issue 2 (2nd April 2020) - Elfering, Lian; van de Grift, Tim C.; Bouman, Mark-Bram; van Mello, Norah M.; Groenman, Freek A.; Huirne, Judith A.; Budiman, Ivo Y. W.; Goijen, Linde D. J.; van Loenen, Dorothea K. G.; Mullender, Margriet G.
Abstract: Background: Masculinizing mastectomy is the most requested gender affirming surgery (GAS) in trans men, followed by genital GAS. Mastectomy and total laparoscopic hysterectomy, with or without bilateral salpingo-oophorectomy (TLH ± BSO), can both be performed in one single operation session. However, data on complication rates of the combined procedure is scarce and no consensus exists on the preferred order of procedures. Aims: To compare safety outcomes between mastectomy performed in a single procedure with those when performed in a combined procedure and assess whether the order of procedures matters when they are combined. Methods: A retrospective chart review was performed of trans men who underwent masculinizing mastectomy with or without TLH ± BSO in a combined session. The effects of the surgical procedure on complication and reoperation rate of the chest were assessed using logistic regression. Results: In total, 480 trans men were included in the study. Of these, 212 patients underwent the combined procedure. The gynecological procedure was performed first in 152 (71.7%) patients. In the total sample, postoperative hematoma of the chest occurred in 11.3%; 16% in the combined versus 7.5% in the single mastectomy group (p = 0.001). Reoperations due to hematoma of the chest were performed in 7.5% of all patients; 10.8% in the combined versus 4.9% in the single mastectomy group (p = 0.017). The order of procedures in the combined group had no significant effect on postoperative hematoma of the chest (p = 0.856), and reoperations (p = 0.689). Conclusion: Combining masculinizing mastectomy with TLH ± BSO in one session was associated with significantly more hematoma and reoperations compared with separately performing mastectomy. This increased risk of complications after a combined procedure should be considered when deciding on surgical options. The order of procedures in a combined procedure did not have an effect on safety outcomes.